Application of Co/Al2O3 Catalyst in Steam Reforming of Glycerol - Cheng, C. K. (2010)
Alumina-supported cobalt catalyst has been employed in a fixed bed reactor for the direct production of synthesis gas from glycerol steam reforming. Physicochemical properties of the Co/Al2O3 catalyst were determined from N2 physisorption, H2 chemisorption, CO2 and NH3-TPD study as well as X-ray diffraction analysis. Both Lewis and Brönsted acid sites are present on the catalyst surface. The acid:basic site ratio is about 6. Glycerol conversion of between 30 to 65% with relatively large H2:CO ratio (6 to 12) and near-stoichiometric values of H2:CO2 ratio (2 to 2.20) were obtained depending on feed composition (30 to 60wt% glycerol mixture). The glycerol consumption rate appeared to be a weak function of glycerol (0.1) and has 0.4 order with respect to the steam partial pressure. Increased glycerol partial pressure led to high carbon deposition (TOC values of 20 to 24%). However, removal of the deposited carbon was essentially complete following a TPO(air)-TPR(H2) scheme.